CORRUPTION CONSCIOUSNESS AS ONE OF THE MAIN CAUSES OF CORRUPTION - A. B. Mardanov (Russian Journal of Economics and Law)
The article presents the results of social research conducted by polling with online-questionnaire, reflecting the assessment of population of causes of corruption.